AN UNUSUAL CASE OF PENILE TUMOR: GIANT SIZED VERRUCIFORM XANTHOMA OF PENIS - Yogarama, Aditya; Hendratno, Josep Joko (Indonesian Urological Association, 2023)
Objective: This study aims to present a case of Verruciform Xanthoma (VX) on penile shaft. Case(s) Presentation: A 60 years old man was admitted to our hospital with a large sized (8cm) cauliflower like tumor on his penile shaft which started to appear 2 years prior to hospital admission. The tumor was continuously getting bigger during that period. The man did not feel any other signs and symptoms. Incision biopsy sample was taken and the histopathologic result was Verruciform Xanthoma. Then the patient took excision circumcision surgery. Discussion: Penile VX is a benign, asymptomatic, warty lesion that can occur in penile shaft, glans, coronal sulcus, and preputium. Its pathological mechanism is still unclear but the most accepted theories are mucocutaneous reaction to localized trauma and chronic inflammation. Due to its atypical appearance, it can be mistaken as other lesion, even a malignant one. Histopathological examination must be done to confirm diagnosis, and to plan the right treatment. We conduct excision and circumcision to compensate a wide skin loss and achieved satisfactory result. Conclusion: Penile VX can be mistaken as a malignant lesion, thus histopathological examination must be done to avoid over radical treatment. Excision and circumcision surgery for large sized penile VX achieve satisfactory result. Keywords: Penile, verruciform xanthoma, tumor.